A Review of Jesus for Everyone: Not Just Christians - Gabrielson, Timothy A. (Christian scholar's review, 2025)
Jesus for Everyone: Not Just Christians AmyJill Levine. Published by HarperOne in 2024. 306 pp. $ 29.99. 9780062216724. Amazon Goodreads.